2017
DOI: 10.1177/1934578x1701200516
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Effects of Essential Oils from Selected Medicinal Plants. Synergy among the Main Components

Abstract: Fourteen essential oils (EOs) from selected live germplasm of medicinal plants have been tested for their antitrypanosomal and cytotoxic activity. These plants have been domesticated and maintained under experimental cultivation. Their EOs were tested on epimastigote forms of Trypanosoma cruzi strain Y and human lung fibroblasts LC5 cell line, along with the major components of the active oils, both separately and in binary combinations. Mentha rotundifolia, Thymus zygis, T. vulgaris and Hyssopus officinalis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…Guardo et al (26) reported moderate trypanocidal effects of an H. officinalis EO from a Spanish hyssop population on T. cruzi with activity levels similar to the ones found here.…”
Section: Effect Of Salinity On the Antiparasitic Activity Of Hyssopussupporting
confidence: 88%
See 2 more Smart Citations
“…Guardo et al (26) reported moderate trypanocidal effects of an H. officinalis EO from a Spanish hyssop population on T. cruzi with activity levels similar to the ones found here.…”
Section: Effect Of Salinity On the Antiparasitic Activity Of Hyssopussupporting
confidence: 88%
“…Among other hyssop EO components, α-pinene showed a moderate effect on T. cruzi (70) and strong effect on T. brucei, while α-phellandrene showed a moderate effect (71). β-Pinene was active against T. cruzi and showed synergistic effect with carvacrol (26). Germacrene D inhibited the enzyme cruzain, a cysteine protease from T. cruzi (72,73) and this compound showed moderate activity against trypomastigote forms (74).…”
Section: Effect Of Salinity On the Antiparasitic Activity Of Hyssopusmentioning
confidence: 97%
See 1 more Smart Citation
“…In the case of thymol, it is demonstrated that it disrupts the permeability of the cell membrane, by increasing the size and number of pores or by disorganization of anionic lipopolysaccharides and, therefore, allows antibiotics, or any substance in combination, penetrate inside the cell and cause the desired effect. [32] Furthermore, previous study on the effects of EO components on T. cruzi, including several tested here (1,8-cineole, p-cymene, β-pinene, linalool, γ-terpinene, thymol), [27] also showed synergistic combinations for the lower concentrations tested (7 combinations at 10 μg/ml) and antagonistic ones at the highest dose (9 combinations at 100 μg/ml). Among the antagonistic combinations, six included 1,8-cineole and five γterpinene, and among the synergistic, four included carvacrol (not tested in the present work) and four terpinene, but no β-pinene.…”
Section: Resultsmentioning
confidence: 56%
“…At the same time Semerdjieva et al [28] identified eucalyptol as a major compound in the essential oil of H. officinalis accounting for 25-59% in the samples. Guardo et al [29] also reported eucalyptol as a major component of the H. officinalis essential oil accounting for 53% of its composition. The composition of the essential oil from H. officinalis could be influenced by a number of factors including climatic conditions and the application of different agronomic practices [30], the use of different subspecies or genotypes as a biomass for essential oil distillation [31] and even the application of different distillation conditions [28].…”
Section: Volatile Diversity In Flowers From Individual Hyssop Plantsmentioning
confidence: 95%